On the Use of Crushed Recycled Glass Instead of Silica Sand in Dual-Media Filters - SOYER, ELİF; AKGİRAY, ÖMER (WILEY, 2013)
Crushed recycled glass was evaluated as an alternative to silica sand in dual-media filters. Pilot scale inline filtration experiments were carried out using raw waters from three different water sources with turbidities between 6.0 and 14.0 NTU. Two physically identical filter columns were operated in parallel in the experiments. One filter consisted of 62.5cm silica sand and 41.5cm anthracite coal, whereas the other filter contained 62.5cm crushed recycled glass plus 41.5cm anthracite coal. The total bed depth was 104cm for both filters. The properties of the media were as follows: Glass effective size=0.77mm, uniformity coefficient=1.41. Sand effective size=0.79mm, uniformity coefficient=1.33. Coal effective size=1.45mm, uniformity coefficient=1.39. Experiments were repeated five times as follows: (i) Without the use of a coagulant, (iiiii) with 5 and 10mg/L of alum, and (ivv) with 5 and 10mg/L of ferric chloride. The filtration rate used was 11.5m/h. Turbidity, particle counts, and head losses were measured and compared as functions of time. The following were observed: (i) Effluent turbidities and particle counts of the two filters were very close, i.e., essentially the same effluent quality was obtained when crushed glass was used instead of silica sand. (ii) In the majority of the tests, the filter with crushed glass generated both a smaller clean-bed head loss and smaller clogging head losses than those of the filter containing sand. It is concluded that crushed glass may be a good alternative to silica sand in dual-media filtration.
Keywords: Crushed glass; Filter media; Head loss; Particle removal; WATER-TREATMENT; WASTE-WATER; PERFORMANCE; FILTRATION